2016
DOI: 10.3906/biy-1601-23
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of peanut phenolic compounds possessing histone deacetylase inhibitory activity on human colon cancer cell lines

Abstract: Phenolic compounds present in our diet play an important role in colon cancer chemoprevention. Previous results demonstrated that peanut testa extract inhibited both histone deacetylase (HDAC) activity and the growth of colon cancer cells. In this study, four identified phenolic compounds in peanut testae (resveratrol, p-coumaric acid, ferulic acid, and sinapinic acid) were investigated for their HDAC inhibitory and anticancer activities against colon cancer cell lines. In vitro study revealed that resveratrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…The differences were particularly expressed in the ferulic acid that was the most abundant phenolic acid in Puno extracts (78% of the total acids) but not identified in Titicaca extract. The results of other authors confirmed a significant cytotoxic effect of ferulic acid against colon cancer cells (Kumnerdkhonkaen et al, 2018; Saenglee, Jogloy, Patanothai, & Senawong, 2016). Furthermore, Zhang et al (2016) based on their research in vitro and in vivo models indicated that the ferulic acid has antitumor potential that could be used as a therapeutic agent against breast cancer.…”
Section: Resultssupporting
confidence: 52%
“…The differences were particularly expressed in the ferulic acid that was the most abundant phenolic acid in Puno extracts (78% of the total acids) but not identified in Titicaca extract. The results of other authors confirmed a significant cytotoxic effect of ferulic acid against colon cancer cells (Kumnerdkhonkaen et al, 2018; Saenglee, Jogloy, Patanothai, & Senawong, 2016). Furthermore, Zhang et al (2016) based on their research in vitro and in vivo models indicated that the ferulic acid has antitumor potential that could be used as a therapeutic agent against breast cancer.…”
Section: Resultssupporting
confidence: 52%
“…In addition, the cell cycle arrest induced by TFs was compared to phenolic compounds p -coumaric acid and resveratrol. According to the results conducted by Saenglee et al, 1000 μM p -coumaric acid could merely enhance the G0/G1-phase cell population by 9.60% in colon cancer cell line HCT-116 cells and 50 μM resveratrol enhanced the G2/M-phase cell population by 5.50% in colon cancer cell line HT-29 cells, which were much lower than TFs. In conclusion, these results indicated that TFs could induce cell cycle arrest to efficiently kill cancer cells.…”
Section: Resultsmentioning
confidence: 93%
“…Sinapinic acid inhibited the growth of several human cancer cells (HT29, HCT116, HeLa and Jurkat cells; IC 50 values = 1.6, 2.1, 0.9 and 2.8 mM, respectively, for 72 h exposure) [ 19 ]. Ferulic acid has been shown to inhibit the growth of several human cancer cells (HT29, HCT116, MCF7 and HeLa cells; IC 50 values = 2.2, 2.1, 4.0 and 0.9 mM, respectively, for 72 h exposure) by apoptosis induction [ 34 , 35 ]. Accordingly, gallic, vanillic, syringic, p -coumaric, ferulic and sinapinic acids may, at least in part, contribute to antiproliferative activity of the extracts from the powder mix of H. cordata fermented broth and P. emblica fruit especially those with relatively high amounts in the extracts ( p -coumaric and ferulic acids).…”
Section: Discussionmentioning
confidence: 99%